2010
DOI: 10.1097/yco.0b013e3283386578
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting depot formulations of naltrexone for heroin dependence: a review

Abstract: Long-acting sustained release formulations of naltrexone are well tolerated and more effective for relapse prevention in heroin addicts than the oral ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 19 publications
0
40
1
2
Order By: Relevance
“…Vivitrol is an injectable extended-release formulation of naltrexone that has recently been approved for the treatment of opioid abuse and dependence. Vivitrol addresses the concern of medication adherence as a monthly injectable formulation and has been shown to be more effective than oral naltrexone (Krupitskya & Blokhina, 2010). This was also shown in a recent Phase 3 clinical trial that confirmed vivitrol's safety and efficacy in the prevention of relapse to heroin use in a cohort of injection drug users.…”
Section: Medication Assited Treatment Utilizing Naltrexonementioning
confidence: 59%
“…Vivitrol is an injectable extended-release formulation of naltrexone that has recently been approved for the treatment of opioid abuse and dependence. Vivitrol addresses the concern of medication adherence as a monthly injectable formulation and has been shown to be more effective than oral naltrexone (Krupitskya & Blokhina, 2010). This was also shown in a recent Phase 3 clinical trial that confirmed vivitrol's safety and efficacy in the prevention of relapse to heroin use in a cohort of injection drug users.…”
Section: Medication Assited Treatment Utilizing Naltrexonementioning
confidence: 59%
“…Although these data are more than a decade old, the extent to which other methods continue to be used before medications are attempted is a crucial question in understanding patterns of use of medications. Relapsers may be particularly challenging for treatment centers, and it may not seem rational to repeat the same therapy if it has already failed and an alternative is available (Krupitsky & Blokhina, 2010). Although the present study does not include data collection from patients, their attitudes are likely signifi cant in accepting medications, and any frustration with the psychosocial treatments that they have observed to help others may facilitate their engagement with medication-assisted treatment (MAT).…”
Section: Facilitators To the Adoption Of Injectable Naltrexonementioning
confidence: 90%
“…Naltrexone implants have been studied most often in Australia and Russia (Krupitsky and Blokhina 2010). Studies of a naltrexone implant in opioiddependent patients in Australia showed a reduction in morbidity and mortality Tait et al 2008).…”
Section: Replacement Followed By Abrupt or Gradual Tapering Of Buprenmentioning
confidence: 99%
“…Recent studies have evaluated the feasibility and effi cacy of sustained naltrexone in the form of intramuscular injections Sullivan et al 2006;Degenhardt et al 2008) or as subcutaneous implants in opioid users (Reece 2007;Hulse et al 2009Hulse et al , 2010Stotts et al 2009;Krupitsky and Blokhina 2010). Although a Cochrane analysis by Lobmeier et al (2008) concluded that there is insuffi cient evidence to recommend sustained-release naltrexone for the treatment of opioid dependence, data from an unpublished study conducted in Russia served as the basis for the approval by the US Food and Drug Administation of a one-month naltrexone formulation for the treatment of opioid dependence.…”
Section: Depot and Implant Naltrexonementioning
confidence: 99%